1997
DOI: 10.1111/j.1553-2712.1997.tb03812.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial Creatine Kinase‐MB Results Are a Sensitive Indicator of Acute Myocardial Infarction in Chest Pain Patients with Nondiagnostic Electrocardiograms: The Second Emergency Medicine Cardiac Research Group Study

Abstract: Objective: To determine the test performance characteristics of serial creatine kinase-MB (CK-MB) mass measurements for acute myocardial infarction (MI) in patients presenting to the ED with chest pain and nondiagnostic ECGs. Methods: A prospective, observational test performance study was conducted. Hemodynamically stable patients aged 2 2 5 years with chest discomfort, but without ECGs diagnostic for MI, were enrolled at 7 university teaching hospitals. Presenting ECGs showing >1 -mV ST-segment elevation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…212,214,249 -251 One study of 1,042 patients found the addition of a 3-h delta CK-MB to result in a sensitivity of 93% and a specificity of 94% for MI. 248 In another study of 2,074 consecutive ED chest pain patients, a 2-h delta CK-MB in conjunction with a 2-h delta troponin I measurement had a sensitivity for acute MI of 93% and specificity of 94% in patients whose initial ECG was nondiagnostic for injury. When combined with physician judgment and selective nuclear stress testing, the sensitivity for MI was 100% with specificity of 82%, and the sensitivity for 30-d ACS was 99.1% with specificity of 87%.…”
Section: Clinical Use Of Marker Change Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…212,214,249 -251 One study of 1,042 patients found the addition of a 3-h delta CK-MB to result in a sensitivity of 93% and a specificity of 94% for MI. 248 In another study of 2,074 consecutive ED chest pain patients, a 2-h delta CK-MB in conjunction with a 2-h delta troponin I measurement had a sensitivity for acute MI of 93% and specificity of 94% in patients whose initial ECG was nondiagnostic for injury. When combined with physician judgment and selective nuclear stress testing, the sensitivity for MI was 100% with specificity of 82%, and the sensitivity for 30-d ACS was 99.1% with specificity of 87%.…”
Section: Clinical Use Of Marker Change Scoresmentioning
confidence: 99%
“…A newer method to both identify and exclude MI within 6 h of symptoms is to rely on changes in serum marker levels (delta values) over an abbreviated time interval (e.g., 2 h) as opposed to the traditional approach of performing serial measurements over 6 to 8 h. 212,214,[247][248][249][250] Because assays are becoming more sensitive and precise, this method permits the identification of increasing values while they are still in the normal or indeterminate range of the assay. By relying on delta values for the identification or exclusion of MI, higherrisk patients with positive delta values can be selected earlier for more aggressive anti-ischemic therapy (e.g., GP IIb/IIIa inhibitors), and lower-risk patients with negative delta values can be considered for early stress testing.…”
Section: Clinical Use Of Marker Change Scoresmentioning
confidence: 99%
“…218,220,[255][256][257] One study of 1042 patients found the addition of a 3-h delta CK-MB to result in a sensitivity of 93% and a specificity of 94% for MI. 254 In another study of 2074 consecutive ED chest pain patients, a 2-h delta CK-MB in conjunction with a 2-h delta troponin I measurement had a sensitivity for acute MI of 93% and specificity of 94% in patients whose initial ECG was nondiagnostic for injury. When combined with physician judgment and selective nuclear stress testing, the sensitivity for MI was 100% with specificity of 82%, and the sensitivity for 30-d ACS was 99.1% with specificity of 87%.…”
Section: Clinical Usementioning
confidence: 99%
“…251 In the TACTICS TIMI-28 study, subgroups of patients with no ECG changes, a low TIMI score, and no cTn elevation showed no benefit from the invasive strategy, whereas those with positive cTn, independent of the presence of elevated CK-MB levels, showed markedly reduced odds of adverse clinical events of 0. 13 A newer method to both identify and exclude MI within 6 h of symptoms is to rely on changes in serum marker levels (delta values) over an abbreviated time interval (eg, 2 h) as opposed to the traditional approach of performing serial measurements over 6 to 8 h. 218,220,[253][254][255][256] Because assays are becoming more sensitive and precise, this method permits the identification of increasing values while they are still in the normal or indeterminate range of the assay. By relying on delta values for the identification or exclusion of MI, higher-risk patients with positive delta values can be selected earlier for more aggressive anti-ischemic therapy (eg, GP IIb/IIIa inhibitors), and lower-risk patients with negative delta values can be considered for early stress testing.…”
Section: Clinical Usementioning
confidence: 99%
“…Creatine kinase-MB (CK-MB) levels help guide disposition decisions and offer prognostic value. 7,8 The cardiac troponins have proven even more valuable in assessing risk and guiding initial treatment. [9][10][11][12][13][14] Hence, ECG findings predictive of positive cardiac markers might be helpful as well.…”
mentioning
confidence: 99%